Periphery as Context: Enlightenment Influences Towards Conceptual Change in Polish-Lithuanian Political Thinking in the Later 18th Century - Mačkinis, Vilius (Baltic Journal of Political Science, 2020)
The specific political culture of the Polish-Lithuanian Commonwealth and its changes, leading to state reforms by the end of the 18th century, require a methodological approach, which would allow understanding the flow and interconnectedness of the ideas between wider European and smaller local contexts. Arguing that entangled history approach allows understanding peripheral contexts better, the article presents specific aspects of the Polish-Lithuanian Enlightenment creating the context for conceptual change in political thinking. The context specific details are presented with the analysis of Vilnius University related discourse showing that the Enlightenment ideas were used to achieve certain goals of local improvement.